Hotspots in action: near-infrared light mediated photoelectrochemical oxygen evolution on high index faceted plasmonic gold nanoarchitectures. Issue 31 (27th July 2022) - Rajagopal, Sanjeevan; Thangudu, Suresh; Feng, June-Yen; Sriram, Pavithra; Yen, Ta-Jen; Hwang, Kuo Chu
Abstract : Near infrared light mediated photoelectrochemical oxygen evolution is demonstrated on novel Au 12 tip nanostructures for the first time. Abstract : Photo-induced electrochemical water splitting is a fascinating approach to overcome the present energy demands as well as environmental issues. To this end, near-infrared (NIR) photocatalysts stand out as promising candidates (where 53% of the solar light is NIR light) to solve the present energy crisis but the lack of NIR-activated photocatalysts has remained a great challenge for decades. Herein, for the first time, we report the synthesis of high-index faceted plasmonic Au nano-branched 12 tip nanostars, which can absorb the whole spectral region of electromagnetic radiation (UV-vis-NIR), for efficient water splitting. Moreover, the plasmonic hot spots on the Au 12 tip nanostars significantly promote the photoelectrochemical oxygen evolution reaction (OER) under NIR light (915 nm) with long-term stability. Remarkably, the Au 12 tip nanostars exhibit 250-fold enhancement of activity under 915 nm laser irradiation and 6.5-fold enhancement of activity under 532 nm laser irradiation, as compared to the Au NPs. Furthermore, the Finite-Difference Time-Domain (FDTD) study confirmed that the significant photoelectrochemical (PEC) enhancement in the NIR light region could be attributed to the hot-electron injection/plasmonic hot spot mechanism upon localized surface plasmonic resonance (LSPR) excitation. Overall, we anticipate that the present work would help to develop new NIR photoelectrocatalysts for meeting future energy demands.